Development of mobile learning application for electricity and magnetism physics on Android platform - Che Abdullah, Che Azurahanim; Mohammad, Azmi; Abdul Wahab, Zaidan (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
This paper presents the design and development of Mobile Learning application for Physics II subject focusing mainly on Electricity and Magnetism Physics. The mobile learning application is developed on Android Platform using Java programming language. The aim is to help students in Physics II course at the Department of Physics, Faculty of Science, Universiti Putra Malaysia. With this mobile application, student could learn and revise the key elements in the topic “Electricity and Magnetism” anywhere and anytime at their own pace. Our approach is to incorporate definition, formula, and animation concept with command language in creating comprehensive, fun and informal environment in presenting Electricity and Magnetism Physics. This mobile learning application intends to complement the requirement for student centred learning and e-learning systems due to the great potential of mobile apps in enhancing students’ learning process.